Sales Growth Throught Quality Cost in Increasing Profit in Micro, Small and Medium Enterprises (MSMEs) - Rustan Rustan (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to determine and analyze sales growth through quality costs in increasing profits in micro, small and medium enterprises (MSMEs) in Makassar City. The approach in this study is a qualitative approach. The type of data used in this study is primary and secondary data. The objects in this study are sales growth, quality costs and profits. The data collection technique used is the method of interviewing several MSMEs regarding sales growth through quality costs. The analysis technique used in this study is descriptive analysis and qualitative data analysis techniques. The steps for data analysis techniques are data reduction, data presentation and drawing conclusions. The results showed that the cost of quality can help increase sales growth in SMEs and significantly affect the lab.